MATRIX METALOPROTEINASE AS A POTENTIAL SALIVARY BIOMARKER FOR ORAL SQUAMOUS CELL CARCINOMA - Santoso, Astrid Widhowaty; Setiadhi, Riani (Universitas Baiturrahmah, 2024)
Introduction: Oral squamous cell carcinoma (OSCC) is the sixth most common cancer worldwide and the most prevalent form of oral cancer. The five-year survival rate for OSCC varies considerably depending on the stage of the disease, ranging from 40% to 60%. The majority of cases are diagnosed at an advanced stage, resulting in a significantly reduced life expectancy. Therefore, there is a clear need for effective strategies to detect cancer at an early stage. Aim: The objective of this article is to identify the potential of matrix metalloproteinase (MMP) as a salivary biomarker for the early detection of oral squamous cell carcinoma (OSCC). Review: Saliva is considered a potential source of biomarkers for oral cancer due to its continuous contact with cancerous lesions in the oral cavity and the various enzymes, hormones, antibodies, antimicrobial constituents, and cytokines it contains. MMP is an extracellular endopeptidase enzyme present in saliva and associated with the carcinogenesis process. It has been identified as a salivary biomarker for the early detection of OSCC. The levels of several MMP proteins in the saliva of OSCC patients have been found to be elevated, including MMP-1, MMP-2, MMP-3, MMP-7, MMP-8, MMP-9, MMP-10, MMP-11, MMP-12, and MMP-13. Conclusion: The increased levels of salivary MMP, which were most specifically found in OSCC patients, included MMP-1, MMP-2, MMP-3, MMP-9, MMP-10, MMP-12, and MMP-13. This suggests that MMP may be a potential salivary biomarker for the early detection of OSCC